**
Question 16 (OR 2
**
**
nd
**
**
question)
**

If y = log (1 + 2t
^{
2
}
+ t
^{
4
}
), x = tan
^{
-1
}
t, find d
^{
2
}
y/dx
^{
2
}

^{
}

^{
}

CBSE Class 12 Sample Paper for 2019 Boards

Paper Summary

Question 1 Important

Question 2

Question 3

Question 4 (Or 1st) Important

Question 4 (Or 2nd)

Question 5

Question 6

Question 7 Important

Question 8 (Or 1st) Important

Question 8 (Or 2nd)

Question 9

Question 10 (Or 1st) Important

Question 10 (Or 2nd)

Question 11 Important

Question 12 (Or 1st)

Question 12 (Or 2nd)

Question 13 (Or 1st) Important

Question 13 (Or 2nd)

Question 14 Important

Question 15

Question 16 (Or 1st)

Question 16 (Or 2nd) Important You are here

Question 17

Question 18

Question 19 Important

Question 20 Important

Question 21 (Or 1st)

Question 21 (Or 2nd) Important

Question 22

Question 23 Important

Question 24 (Or 1st)

Question 24 (Or 2nd) Important

Question 25

Question 26 (Or 1st) Important

Question 26 (Or 2nd)

Question 27 (Or 1st) Important

Question 27 (Or 2nd) Important

Question 28

Question 29 Important

Class 12

Solutions of Sample Papers and Past Year Papers - for Class 12 Boards

Last updated at Sept. 24, 2021 by Teachoo

Hello! Teachoo has made this answer with days (even weeks!) worth of effort and love. If Teachoo has been of any help to you in your Board exam preparation, then please support us by clicking on this link to make a donation

**
Question 16 (OR 2
**
**
nd
**
**
question)
**

If y = log (1 + 2t
^{
2
}
+ t
^{
4
}
), x = tan
^{
-1
}
t, find d
^{
2
}
y/dx
^{
2
}

^{
}

^{
}

Hello! Teachoo has made this answer with days (even weeks!) worth of effort and love. If Teachoo has been of any help to you in your Board exam preparation, then please support us by clicking on this link to make a donation

Question 16 (OR 2nd question) If y = log〖(1+2𝑡^2+𝑡^4)〗, x = tan^(−1)𝑡, find (𝑑^2 𝑦)/(𝑑𝑥^2 ) Finding 𝒅𝒚/𝒅𝒕 y = log〖(1+2𝑡^2+𝑡^4)〗 𝑑𝑦/𝑑𝑡 = 1/((1 + 2𝑡^2 + 𝑡^4 ) ) × 𝑑(1 + 2𝑡^2 + 𝑡^4 )/𝑑𝑡 𝑑𝑦/𝑑𝑡 = ((4𝑡^3 + 4𝑡))/((1 + 2𝑡^2 + 𝑡^4 ) ) 𝑑𝑦/𝑑𝑡 = (4𝑡(𝑡^2 + 1))/(((𝑡^2 )^2 + 2𝑡^2 + 1^2 ) ) 𝑑𝑦/𝑑𝑡 = (4𝑡(𝑡^2 + 1))/(𝑡^2 + 1)^2 𝑑𝑦/𝑑𝑡 = 4𝑡/((𝑡^2 + 1) ) Finding 𝒅𝒙/𝒅𝒕 x = tan^(−1)𝑡 𝑑𝑥/𝑑𝑡 = 1/(1 + 𝑡^2 ) Now, 𝑑𝑦/𝑑𝑥 = (𝑑𝑦/𝑑𝑡)/(𝑑𝑥/𝑑𝑡) 𝑑𝑦/𝑑𝑥 = (4𝑡/((𝑡^2 + 1) ))/(1/(1 + 𝑡^2 )) 𝑑𝑦/𝑑𝑥 = 4𝑡/((𝑡^2 + 1) )×((1 + 𝑡^2))/1 𝑑𝑦/𝑑𝑥 = 4t Now, (𝑑^2 𝑦)/(𝑑𝑥^2 ) = (𝑑(4𝑡))/𝑑𝑥 = (𝑑(4𝑡))/𝑑𝑥 × 𝑑𝑡/𝑑𝑡 = (𝑑(4𝑡))/𝑑𝑡 × 𝑑𝑡/𝑑𝑥 = 4 × 𝑑𝑡/𝑑𝑥 = 4 × 1/(𝑑𝑥/𝑑𝑡) = 4 (1 + t2) As 𝑑𝑥/𝑑𝑡 = 1/(1 + 𝑡^2 ) 𝑑𝑡/𝑑𝑥 = (1 + t2)